The Latest Reports in Managing Acidic Sludge of Used Motor Oil Reprocessing Industries - Hassanpour, Malek (The Global Environmental Engineers, 2020)
Used Motor Oils Recycling (UMOR) can be fulfilled in different ways depending on the quality and quantity of the fresh oil and the quality of the collected UMO. The Acidic Sludge (AS) is a byproduct of UMOR with hazardous effects and impacts on the environment. It yields 0.15 of each barrel (220 liters) of UMOR operation. The valid and relevant databases were used to discover the latest reports in managing the AS of UMOR operation. The findings of the current review were oriented towards the physical-chemical backbone of AS and its industrial exploitation. The chemical structure of AS was highlighted by a glance view in the recent reports. To sum up, it was recommended to utilize this valuable byproduct in many industrial applications as an additive.